Ethnomathematics in Nepal: A Review of Literature on Indigenous Mathematical Practices among the Magar Community (Shaheed Smriti Journal, 2025)
This study examined the indigenous mathematical practices of the Magar community in Nepal, focusing on their application in agriculture, architecture, and trade. Ethnomathematics offers insights into culturally embedded numerical and spatial reasoning, highlighting how communities develop practical problem-solving strategies. A comprehensive literature review was conducted, synthesizing findings from published studies, ethnographic reports, and historical documents related to Magar practices. The analysis revealed that the community employed intricate measurement systems for land division, geometric principles in traditional construction, and numerical methods in trade and barter. These practices reflect both functional utility and cultural transmission of knowledge across generations. Findings indicate that integrating ethnomathematical knowledge into contemporary education could foster culturally relevant pedagogy and preserve indigenous knowledge systems. The study concludes that Magar mathematical practices exemplify the dynamic interplay between culture and cognition, offering implications for curriculum development, heritage preservation, and further research on indigenous mathematical reasoning.